Penguatan Literasi Baca Siswa Melalui Pemanfaatan Pojok Baca di SD Inpres 1 Malawei Kota Sorong - Hasanudin Hasanudin; Irfandi Idris; Ahmad Wael; Andi Maryam; Rizky Ekawaty Ahmad; Sulkipli M; Nurwaida Nurwaida (FKIP, Universitas Palangka Raya, 2023)
Reading is important in the teaching and learning process. Reading is the process of absorbing knowledge through reading or writing. This study aims to improve students' literacy skills by holding a reading corner in each class and is expected to increase students' interest in reading and increase knowledge that can be a provision in the future. The lack of interest in reading at SD Inpres 1 malawei, due to the lack of reading space and motivation for students such as in grade 6 who should have been prepared to take the graduation exam to continue to the next level of education, namely junior high school but cannot read. This is our shared responsibility between students, teachers and parents in order to increase students' interest in reading, especially in SD inpres 1 malawei so we conduct research in order to increase students' interest in reading and make it a provision in the next level of education and even in the future.